Comparative effectiveness of electroacupuncture VS neuromuscular electrical stimulation in the treatment of chronic low back pain in active-duty personals: A single-center, randomized control study - Meng, Xiao-yan; Bu, Lan; Chen, Jia-ying; Liu, Qiu-jia; Sun, Li; Li, Xiao-long; Wu, Fei-xiang (Frontiers in Neurology, 2022)
Introduction Low back pain (LBP) is the most prevalent form of chronic pain in active-duty military personnel worldwide. Electroacupuncture (EA) and neuromuscular electrical stimulation (NMES) are two most widely used treatment methods among military, while evidence for benefits of them are lacking. The aim of this randomized clinical trial is to investigate the effectiveness of EA versus NMES in reducing pain intensity among active-duty navy personals with chronic LBP. Methods The study is designed as a single-center, randomized controlled trial. The primary outcome is a positive categorical response for treatment success in the first-time follow-up, which is predesignated as a two-point or greater decrease in the NRS score and combined with a score greater than 3 on treatment satisfaction scale. Second outcomes including pain intensity; rate of treatment success; Oswestry Disability Index (ODI) fear-avoidance beliefs questionnaire (FABQ) score along with muscular performance. The first follow-up starts in one day after completing the last treatment session, and then the 4-week and 12-week follow-up are applied via telephone visit. Results 85 subjects complete the treatment diagram and include in the analysis. For primary outcome, no difference has been found between EA and NMES, with 65.1% (28 in 43) individuals report positive response to EA treatment while 53.5% (23 in 43) in the NMES. However, for longer follow-ups, superiority in positive response of EA has been found in 4-week (26 in 39, 66.7% vs. 16 in 40, 40%; P=0.018) and 12-week (24 in 36, 66.7% vs. 12 in 36, 33.3%; P=0.005). In the regression analysis, baseline pain intensity and FABQ score are identified to be highly associated with positive treatment outcomes. Finally, the subgroup analysis suggests that EA treatment is associated better long-term outcomes in LBP patients with severe pain score (NRS score>4, Figure 4B) and stronger fear-avoidance beliefs. Conclusions Both of the EA and NMES are associated with positive response in treating military LBP, and the former offers lasting benefits. Thus, electroacupuncture is a more recommended treatment for military LBP. More researches are needed to verify an efficient and standardized treatment session, with more information and evidence about indications for these treatments.